2019
DOI: 10.15376/biores.14.3.demuner
|View full text |Cite
|
Sign up to set email alerts
|

Biorefinery review: Wide-reaching products through kraft lignin

Abstract: This review details the structure of lignin and curates information on the characteristics that this polymer must have for each specific use. Lignin is a by-product of the pulp and paper industry and the second most abundant biopolymer after cellulose. Approximately 50 million tons of lignin are produced worldwide annually, of which 98% to 99% is incinerated to produce steam, process energy. Just 1% to 2% of the lignin, derived from the sulfite pulp industry, is used in chemical conversion to produce lignosulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
64
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 201 publications
0
64
0
1
Order By: Relevance
“…29 Nowadays, the 1 st scenario is still the major application for technical lignin and Every year, from the principal 250 Mt, about ~70 Mt of technical lignin are separated, of which an estimated 95 % are burned to produce energy. 38,39 Among this quantity, approximately 2 Mt/y are only by the sulfite process. 21,38 In the sulfite pulping, debarked wood chips are treated with sulfite and bisulfite salts solution (Na is the major counter-ions to bisulfite) in acidic aqueous media (pH 1-5) at temperatures ranging from 125 to 190°C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Nowadays, the 1 st scenario is still the major application for technical lignin and Every year, from the principal 250 Mt, about ~70 Mt of technical lignin are separated, of which an estimated 95 % are burned to produce energy. 38,39 Among this quantity, approximately 2 Mt/y are only by the sulfite process. 21,38 In the sulfite pulping, debarked wood chips are treated with sulfite and bisulfite salts solution (Na is the major counter-ions to bisulfite) in acidic aqueous media (pH 1-5) at temperatures ranging from 125 to 190°C.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 Among this quantity, approximately 2 Mt/y are only by the sulfite process. 21,38 In the sulfite pulping, debarked wood chips are treated with sulfite and bisulfite salts solution (Na is the major counter-ions to bisulfite) in acidic aqueous media (pH 1-5) at temperatures ranging from 125 to 190°C. 21,40 Within this process, the ether bonds in lignin are partially hydrolyzed and followed by sulfitization step (introducing -SO 3functionalities), or oxidative coupling to form parasitic C-C bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide lignin production is approximately 50 million tons [31] by-product have distinct adhesive characteristics and may be used as a densification binder [29]. The use of lignin as binder is relatively new and studies of this application as a binder have been done recently [28] [29] [32]- [38].…”
Section: Introductionmentioning
confidence: 99%
“…High encapsulation would be achieved when the core/shell mass ratio was 2:1, and 10 wt% of the crosslinking monomer pentaerythritol tetraacrylate (PETRA) was used (49). Recent studies have shown that kraft lignin can also function as dispersants, bioplastics, and fuel for transportation (50).…”
Section: Introductionmentioning
confidence: 99%